Mutations in the AUH gene cause 3-methylglutaconic aciduria type I - Ly-Hartig, Thi Bach Nga; Peters, Verena; Gibson, K. Michael; Liesert, Michael; Buckel, Wolfgang; Wilcken, Bridget; Carpenter, Kevin; Ensenauer, Regina; Hoffmann, Georg F.; Mack, Matthias; Zschocke, Johannes (Human mutation, 2003)
The conversion of 3-methylglutaconyl-CoA to 3-hydroxy-3-methylglutaryl-CoA is the only step in leucine catametabolism yet to be characterized at enzyme and DNA levels. The deficiency of the putative mitochondrial enzyme 3-methylglutaconyl-CoA hydratase associates with the rare organic aciduria 3-methylglutaconic aciduria type I (MGA1), but neither the enzyme nor its gene have been described in any organism. Here we report that human 3-methylglutaconyl-CoA hydratase is identical with a previously described RNA-binding protein (designated AUH) possessing enoyl-CoA hydratase activity. Molecular analyses in five patients from four independent families revealed homozygosity or compound heterozygosity for mutations in the AUH gene; most mutations are predicted to completely abolish protein function. Mutations identified include c.80delG, R197X, IVS8-1G>A, A240V, and c.613_614insA. Clinical severity of MGA1 in published patients has been quite variable. Included in the present study is an additional patient with MGA1 who was detected by neonatal screening and has remained asymptomatic up to his present age of 2 years. The boy is homozygous for an N-terminal frameshift mutation in the AUH gene. Complete absence of 3-methylglutaconyl-CoA hydratase/AUH appears to be compatible with normal development in some cases. Further work is required to identify external or genetic factors associated with development of clinical problems in patients with MGA1. Hum Mutat 21:401-407, 2003. © 2003 Wiley-Liss, Inc.
Gesehen am 22.12.2020